Rust - Monica L. Elliott; Philip F. Harmon (EDIS)
Rust is a fungal disease that occurs in cool weather causing yellow specks enlarging to spots with orange pustules in St. Augustinegrass and zoysiagrass. This revised 2-page fact sheet was written by M. L. Elliott and P. F. Harmon, and published by the UF Department of Plant Pathology, February 2011.